A prosthesis user perspective on interactions with their prosthetist during lower-limb prosthetic socket fitting. - Armitage, Lucy; Turner, Shruti; Ford, Belinda; McDonald, Kirsty A.; Sparke, Darrel; Kark, Lauren (Prosthetics & Orthotics International, 2026)
Background: Successful prosthetic socket fitting contributes to prosthesis user satisfaction and facilitates rehabilitation, but is often challenging to achieve and maintain. There is a lack of information available that explores firsthand experiences of prosthetic users throughout socket fitting sessions and, in particular, their preferences regarding information exchange between them and their prosthetist. Objectives: Assess satisfaction with prosthetic service, confidence in clinical judgement, and confidence providing feedback to prosthetists, examine experiences of prosthesis users in providing feedback to prosthetists and identify the types of information that prosthesis users want to communicate to their prosthetist, as well receive before, during, and after the socket fitting process. Study Design: Mixed-method (quantitative and qualitative) survey. Methods: A questionnaire was designed and administered in consultation with Amputees NSW (an amputee community support group) and distributed through their membership database. Quantitative items with discrete or scale-based responses were analyzed using descriptive, nonparametric methods and described satisfaction and confidence during prosthetic fitting. A thematic analysis was performed on qualitative responses to explore prosthesis user experiences of information exchange before, during, and after socket fitting. Results: There were 24 survey responses. Ninety-six percentage of respondents were satisfied with their prosthetic service and were confident in their prosthetists' clinical judgement as well as ensuring socket comfort for their client. Most prosthesis users felt comfortable to provide feedback to their prosthetist (median =100 [interquartile range = 20], where 0 = not at all confident and 100 = completely confident). Experiences in providing input on comfort and fitting fell under 4 interrelated themes: collaboration, frustrations with process, impacts of poor fit, and prosthetic fit. Experiences with exchanging information with their prosthetist before, during, and after socket fitting fell under a further 4 themes: process-based information and provision options, taking history and treatment planning, collaboration and communication, and functional concerns. Conclusions: Prosthesis users' confidence to provide feedback and satisfaction with prosthetic services could be helped by ensuring a responsive working relationship, facilitating information exchange between the prosthetist and prosthesis user, as well as improved prosthesis user education on the socket fit process.